Edukasi Upaya Pencegahan dan Deteksi Dini Kanker Serviks berbasis Media Video Animasi dan Flipcharts untuk Pelajar Kota Malang - Rachmawati, Windi Chusniah; Ratih, Suci Puspita; Ekawati, Rany (citeus, 2021)
In general, cancer consists of cells that divide uncontrollably. Cervical cancer is caused by HPV, or Human Papilloma Virus. Every 2 minutes worldwide, a woman dies from cervical cancer, while in Indonesia it happens every 1 hour. All women are at risk of developing cervical cancer, including adolescent girls who will marry and give birth, thereby increasing their risk of cervical cancer. This community service aims to increase students' knowledge about prevention efforts and early detection of cervical cancer through health promotion media. The community service was conducted randomly on 20 female students who were willing to serve as respondents. Community service delivered through health animation video media and flipchart calendars can increase students' knowledge about prevention efforts and early detection of cervical cancer.